Possible Risk Factors of Pulmonary Metastases in Patients With International Federation of Gynecology and Obstetrics Stage I Endometrioid-Type Endometrial Cancer. Issue 6 (1st July 2017) - Jiang, Wei; Chen, Jun; Tao, Xiang; Huang, Feifei; Zhu, Menghan; Wang, Chao; Feng, Weiwei
Abstract : Objective: Limited data have been obtained in regard to pulmonary metastasis (PM) in patients with stage I endometrial cancer. The aims of the study were (1) to present the clinical and pathological characteristics of patients with PM in the setting of stage I endometrioid-type endometrial cancer (EEC) and (2) to define possible factors that may be used to predict PM. Methods: Six hundred thirty patients with stage I EEC, including 12 with PM, 19 with extra-PM (EPM), and 599 with no recurrence, were observed. Paired samples of primary and metastatic tumors from a patient were used for exome sequencing to identify potential gene mutations associated with PM. Results: There was no significant difference in the age, Ki-67, lymphatic vascular space invasion, and grade 3 among the 3 groups ( P > 0.05). More squamous epithelial differentiation was observed in PM (7/12), as compared with patients with EPM (1/19) ( P < 0.05) and no recurrence (20/599) ( P < 0.05). The tumor size of the patients with PM was bigger than that of nonrecurrent patients (29.8 ± 16.6 vs 18.5 ± 16.3 mm, P < 0.05). More percentage of patients with deep myometrial invasion (IB) were found in PM (6/12) ( P < 0.05) as compared with patients with EPM (3/19) ( P < 0.05) and no recurrence (76/599). CDH10, ARID1A, and EMT-associated gene mutations were identified in metastatic tumor tissue but not in primary tumors from a patient with EEC and lung metastases. Conclusions: Squamous epithelial differentiation, large tumor size, and deep myometrial invasion might be risk factors for PM in patients with stage I EEC. CDH10, ARID1A, and EMT-associated gene mutation may promote the initiation of lung recurrence. However, further studies are needed to determine the precise mechanisms associated with lung metastasis in these patients.